Thermochemical recovery technology for improved modern engine fuel economy – part 1: analysis of a prototype exhaust gas fuel reformer. Issue 44 (16th May 2015) - Fennell, D.; Herreros, J.; Tsolakis, A.; Cockle, K.; Pignon, J.; Millington, P.
<x xml:space="preserve">Abstract</x> Exhaust gas fuel reforming has the potential to improve the thermal efficiency of internal combustion engines, as well as simultaneously reduce gaseous and particulate emissions.